Efficiency and Collaboration in Hardware Development: A Lean Approach : Case Study - Edfelt, Michael (My University, 2023)
Companies strive towards perfection in their product development processes and want to stay as competitive as possible. In order to achieve that objective, emphasis needs to be put on streamlining the process. Therefore, this thesis explores the Lean methodology from a product development perspective and showcases the effectiveness of the value stream mapping (VSM) and design structure matrix (DSM). The research is executed at a company specialising in energy and marine power solutions and is outlined as a case study. Several research angles have been utilised, which enabled the recognition of diversity in the collected data and information. The methodology is divided into two primary elements: 1) analysing a case project from a component functionality and managerial perspective, and 2) executing a value stream analysis of the hardware development process, which is utilised to develop automation components for complex power solutions. The qualitative research focuses on achieving a holistic understanding of a hardware development process (HWDP) through VSM and DSM. Quantitative data can mainly be seen in the case project analysis, where the output is formed on historical data from an application lifecycle management system and Internal documentation platform. In line with the methodology, the thesis aimed to answer the following research questions: RQ1: How can the process be streamlined by identifying inefficiencies and proposing improvements? RQ2: How can cooperation and collaboration be improved to reduce overall development lead time? The results of the thesis are categorised based on the research methodology’s two primary elements. The project analysis and current state findings have identified the challenges related to outsourcing, communication, collaboration, and technological knowledge gaps. A cross-functional VSM allowed for capturing the information flow between the departments and identifying the wastes and bottlenecks in the process. A value assessment resulted in 47 VA, 16 RNVA, and 8 NVA activities. The NVA activities were analysed, and improvement suggestions were generated, focusing on stakeholder communication, supplier relationships, testing processes, change management, release meetings, and field testing. The DSM enabled the visualisation of dependencies between tasks and structural changes with partitioning. Based on simulations comparing the structural changes between the two DSMs, a 50 % decrease in lead time was identified. However, the implementation feasibility of the new structure is unclear, and further evaluation must be carried out in collaboration with the stakeholders. The thesis uncovered five managerial implications related to holistic process overview, effective outsourcing, improved in-house expertise, robust project planning and scheduling, and continuous improvement. This comprehensive efficiency analysis of the HWDP can be considered a success as it has pinpointed the crucial aspects that can be utilised to achieve an optimal future state of the process.
Keywords: product development; process assessment; case study; evaluation; fi=Sähkö- ja energiatekniikka|en=Electrical Engineering and Energy Technology|; Master´s Programme in Smart Energy